Bone Marrow Aspirate and Biopsy: An Instructional Video - Jennifer C. Kesselheim (Association of American Medical Colleges, 2011)
Abstract Hematologists and oncologists perform bone marrow aspirates and biopsies to evaluate and diagnose hematological malignancies and other disorders of the blood. These procedures are also useful in assessing patients' response to therapies and to determine future management. This resource is an instructional video aimed to teach hematology and oncology clinicians how to perform bone marrow aspirates and biopsies. This video provides fellows with additional opportunities to study the skills needed to perform these procedures safely and competently and allows them to learn without exposing patients to additional burden or risk. In addition, the video can be used for more senior clinicians, such as attending physicians or nurse practitioners, who intend to refresh or update their procedural skills. This instructional video represents an important advance in hematology and oncology education. Rather than practicing these procedures solely at the bedside of patients, this video will allow learners in different disciplines (physicians and nursing) and across the continuum of education (fellows and faculty) to enhance their procedural skills conveniently, efficiently, and without adding additional burdens to our patients.